2005
DOI: 10.1086/428591
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Severe Acute Respiratory Syndrome–Associated Coronavirus Infections in Taiwan

Abstract: Background. In 2003, Taiwan experienced a series of outbreaks of severe acute respiratory syndrome (SARS) and 1 laboratory-contamination accident. Here we describe a new phylogenetic analytical method to study the sources and dissemination paths of SARS-associated coronavirus (SARS-CoV) infections in Taiwan.Methods. A phylogenetic analytical tool for combining nucleotide sequences from 6 variable regions of a SARS-CoV genome was developed by use of 20 published SARS-CoV sequences; and this method was validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 23 publications
(32 reference statements)
0
21
0
Order By: Relevance
“…In addition, different levels of urbanization may affect access to hospitals. The effect of other factors, such as the SARS outbreak in Asia‐Pacific in 2003, also appeared to have a marked impact on the rates, at least in Hong Kong and Taiwan 18,19 . However, the relative impact of these differences are unknown for the different countries.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, different levels of urbanization may affect access to hospitals. The effect of other factors, such as the SARS outbreak in Asia‐Pacific in 2003, also appeared to have a marked impact on the rates, at least in Hong Kong and Taiwan 18,19 . However, the relative impact of these differences are unknown for the different countries.…”
Section: Discussionmentioning
confidence: 99%
“…First, two major subsequent outbreaks in Hong Kong, one at the Amoy Gardens estate and the other at a local hospital, were demonstrated to be directly linked to the SSE in Hotel M. 239,247 Second, phylogenies suggested that the Taiwan outbreaks were likely to be derived from multiple sources, 248,249 including the Amoy Gardens outbreak 250,251 and the SSE in Hotel M. 252 Third, the Singapore outbreak was traced to two separate initial introductions, but both were directly linked to the SSE in Hotel M. 240,253 Finally, in Beijing, although the first case was reported approximately a week after the SSE in Hotel M, 254 phylogenetic analyses suggested that not all of the cases there were related to the SSE in Hotel M and that some of these cases probably originated from Guangdong before the SSE in Hotel M. 255 c. Sporadic re-emergence In December 2003, four independent SARS cases were reported. 256 Phylogenetic analyses of human SCoVs from these cases and civet SCoVs collected from the same period formed a monophyletic cluster that was distinct from the 2002-2003 epidemic cluster.…”
Section: Molecular Epidemiology Of Sars Outbreaksmentioning
confidence: 99%
“…However, the role of civets as a potential natural reservoir host was less evident and eventually ruled out by several studies. Serological studies indicated that only civets in the markets were infected with SARS-CoV, whereas the populations of civets in the wild or on farms are free of major infections (Tu et al, 2004;Lan et al, 2005;Poon et al, 2005). Civets produced overt clinical syndromes when experimentally infected with SARS-CoV (Wu et al, 2005).…”
Section: Natural Reservoirs Of Sars-covmentioning
confidence: 99%
“…Analysis of all the viral sequences available from human patients and animals revealed two major hallmarks of rapid virus evolution during the initial stages of the 2002À2003 outbreaks: (1) All isolates from early patients and market animals contained a 29-nt sequence in ORF8 that is absent in most of the publicly available human SARS-CoV sequences derived from later phases of the outbreaks; (2) a characteristic motif of single-nucleotide variations (SNVs) were identified in SARS-CoV of different phases, and all these SNVs were located in the S gene that codes for the spike protein responsible for attachment to host cellular receptor . All SARS-CoV isolates from epidemic countries and regions outside the mainland China could be traced to Guangdong or Hong Kong based on the S-gene SNV motif (Lan et al, 2005;Tang et al, 2007).…”
Section: Rapid Adaptation Of Sars-covs In Humansmentioning
confidence: 99%